Community profiling focus group: An empowering tool for immigrant community groups. Issue 3 (3rd July 2022) - Mebane, Minou Ella; Benedetti, Maura
Abstract: Community psychology profiling, a complex and lengthy intervention methodology, can play an important role in enhancing social cohesion and integrating immigrants into local communities. In this pilot research intervention, we wanted to investigate if the Community Profiling Focus Group, which is flexible and a less time-consuming methodology could be employed to initiate empowering processes in marginalized community groups such as immigrants. Five focus groups were carried out with different immigrants. Overall our research shows that, though immigrants had deep concerns mostly on work issues and low acceptance of foreigners, participating in the Community Profiling Focus Group enabled them to be more proactive and to identify objectives they could reach jointly to increase their empowerment and integration in their communities.